STRATEGI GURU DALAM UPAYA MENINGKATKAN MINAT BACA SISWA SEKOLAH DASAR - Della Nathalia Desiana; Endang M Kurnianti; Susi Winarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine various strategies used by teachers to increase reading interest in elementary school students, and to analyze the effectiveness of these strategies. By understanding the approaches used by teachers and their impact on students' reading habits, it is hoped that this study can contribute to the development of more literate and innovative educational practices. The results of the study showed that teachers implemented various strategies to increase students' reading interest, including story-based learning, the use of visual and digital media, giving creative reading assignments, and getting used to reading before lessons began. These strategies have been proven to be able to gradually increase students' reading interest and encourage their active involvement in the learning process. Supporting factors in implementing the strategy include the availability of interesting reading materials and support from the school. Inhibiting factors include the lack of adequate library facilities and students' low initial interest in reading activities. This study concludes that the role of teachers is very important in shaping a culture of literacy in elementary schools. Therefore, it is recommended that schools provide further training for teachers in developing literacy strategies, as well as increasing the provision of supporting facilities to support the continuous increase in students' reading interest.